The Wound Healing Effect of Nanoclay, Collagen, and Tadalafil in Diabetic Rats: An In Vivo Study. (15th January 2022) - Ordeghan, Allahyar Noori; Khayatan, Danial; Saki, Mohammad Reza; Alam, Mostafa; Abbasi, Kamyar; Shirvani, Hossein; Yazdanian, Mohsen; Soufdoost, Reza Sayyad; Raad, Haidar Taimouri; Karami, Ali; Tebyaniyan, Hamid
Abstract : The diabetic wound is the most challenging one to manage, which is associated with microvascular and macrovascular dysfunction, and novel strategies such as using hydrogels demonstrate their promising prospect in treatment and management approaches of the diabetic wound. This study aimed to investigate the effect of collagen/nanoclay/tadalafil hydrogel on wound healing in diabetic rats under HIIT exercise. Hydrogel was synthesized, and then biocompatibility and antibacterial tests were performed. The therapeutic effect of collagen/nanoclay/tadalafil hydrogel was assessed after induction of diabetes in the rat model, and wound healing was evaluated with macroscopic and microscopic tests. The result of the MTT test showed no significant cytotoxicity of collagen/nanoclay/tadalafil hydrogel. Furthermore, the inhibitory effect of hydrogel was detected on E . coli and S . aureus . The macroscopic results demonstrated that the wound contraction was considerable in the hydrogel/HIIT exercise and hydrogel groups compared with the HIIT exercise and control groups during 21 days. The microscopic results showed that the presence of fibroblasts, the amount of collagen, the epidermis density, and the formation of hair follicles were increased in the hydrogel/HIIT exercise group compared with other groups in the diabetic rate model. It can be concluded that collagen/nanoclay/tadalafil hydrogel with HIIT exercise could accelerate diabetic wound healing and can be an appropriate candidate for skin regeneration in medical applications.